Tintoretto in the city of La Plata? Several investigations for the reattribution of the Portrait of Melchior Michael to Tintoretto - Romano, Rosana Mariel (2023)
The records of the Museo Provincial de Bellas Artes “Emilio Pettoruti” (Provincial Museum of Fine Arts of Buenos Aires "Emilio Pettoruti") indicate that a work belonging to Jacopo Comin, "Tintoretto," is part of its cultural heritage, of great value to the museum and the university city of La Plata. Over time, and perhaps due to the ambitious nature of this attribution, the original assertion was called into question. Now, taking into account a comprehensive spectroscopic analysis using Raman and FTIR-ATR techniques, in which cinnabar (HgS), lead white (2PbCO3.Pb(OH)2), calcite (CaCO3), gypsum (CaSO4.2H2O), and carbon black were determined, along with tracking the artwork and its journey to the city of La Plata, we are able to affirm the validity of the work, the Portrait of Melchior Michael, reconfirming and reattributing it to the colossal Jacopo Comin, Tintoretto.